Racialization, colonialism, and imperialism: a critical autoethnography on the intersection of forced displacement and race in a settler colonial context - Ma, Jennifer (Frontiers in Sociology, 2023)
Migration has been identified as a priority area for policy responses by both the federal and provincial/territorial governments yet, much of our knowledge about migration is not premised on addressing current xenophobic and racist narratives about migrants. The purpose of this research is an interrogation of Canada's colonialism, imperialism, and racialization, which produce specific oppressive policies and practices that have impacted my family. This research is premised on the understanding that in the space between what is known about migration in Canada and what is not, a great deal of narrative and interpretive work is done that makes assumptions about migrants, specifically forcibly displaced people from the Global South. Through a critical autoethnography focused on my lived experiences as a descendant of forcibly displaced Chinese-Vietnamese people living in a settler colonial nation state, this study critiques to what extent these assumptions are founded, and to what extent they represent a socio-political climate in which migration is set out as particular problems requiring a legal and policing solution. In particular, my analysis centers anti-colonialism and anti-racism, shifting to resistance to systemic violence and liberation, while considering the discursive and on-the-ground effects of racist, colonial, and imperial policies and practice. Set against the backdrop of the rise of white nationalism, xenophobia, and racism across all levels of government and academia, and the general public, the results of this study produce a counter-narrative focused on the intersection of forced displacement and race in a settler colonial context, which is both timely and urgent.